Implementation of Polite Language Education in Elementary Schools (International Conference on Elementary Education, 2018)
Human civilization that moves dynamically does not escape from the influence of globalization that affects education, especially in polite language education which if the implementers and users of language politeness have decreased in the implementation of education. then polite language education requires education in achieving goals where polite language is an educational effort in shaping individual personalities that are able to overcome the problems of life in the world. Mechanistic education has an impact on the language politeness that a child has toward his maturity. Courteous language education is one of the important alternatives in realizing Indonesian human beings who are afflicted by moral decadence in the implementation of polite language education has its own challenges that expect polite language actions not just the choice of words right in speaking but an individual character that reflects the values ??prevailing in society, and polite language education is one of the values ??that must be inculcated in character education from an early age in school education.